Does IFRS information on tax loss carryforwards and negative performance improve predictions of earnings and cash flows? - Sandra Dreher; Sebastian Eichfelder; Felix Noth (Arbeitskreis Quantitative Steuerlehre (arqus), 2022)
We analyze the usefulness of accounting information on tax loss carryforwards and negative performance to predict earnings and cash flows. We use hand-collected information on tax loss carryforwards and the corresponding deferred taxes from the International Financial Reporting Standards tax footnotes for listed firms from Germany. Our out-of-sample tests show that considering accounting information on tax loss carryforwards does not enhance the accuracy of performance predictions and even worsens predictions. Besides, common forecasting approaches that deal with negative performance are prone to prediction errors. We provide a simple empirical specification to reduce forecast errors. We find evidence that more elaborate machine learning models (least absolute shrinkage and selection operator method) typically do not perform better or even worse than our simple specification in out-of-sample tests.
Keywords: M40; M41; C53; 330; performance forecast; out-of-sample tests; deferred tax assets; tax loss carryforwards